Rainwater harvesting: the possibilities of an integrated network in urban communities based on people’s perceptions, attitudes, and neighborly efforts - Wedel, Shaedon (Kansas State University, 2023)
Climate change consequences such as drought and flooding and how they affect urban neighborhoods have been pressing issues over the past few decades. Due to historically marginalized communities' lack of resources, there has been concern for how these climate event factors play into the demand for water (Haque et al., 2016). Rainwater harvesting – collecting rainwater runoff from a catchment source and using it for the benefit of humans - is a method to address this issue. (Sivanappan, 2006; Hillel, 2005; Geetha, 2022 p. 102). While rainwater harvesting has been explored, less attention has been paid to the functional use of the water, and the attitudes and perceptions of the users of the systems. This is important due to the lack of water resources available to low-income neighborhoods and how rainwater can be utilized to mitigate water insecurity (Bathke, 2022). The aim of this study is to explore how the use of collected rainwater and attitudes and perceptions of the users can help with increased implementations of integrated rainwater harvesting systems. This study considers eight neighborhoods of Eastside Kansas City, Missouri as a case to examine how a variety of land-use types in low-income neighborhoods respond to various functional uses of collected rainwater and their attitudes and perceptions of such systems. Observation, mapping, and semi-structured interviews were used to collect data from residents through random sampling of three land-use categories supported by the observation and mapping: 1) Cultural and Educational Institutes, 2) Industrial, Restaurant, and Retail, and 3) Residential and Living Centers. Semi-structured interviews were performed with fifteen participants in the study area. The data analysis showed there is an overall concern of local drought and flooding across all categories, with no immediate concerns of water availability. It also showed that approximately one-third of participants had no knowledge about rainwater harvesting. After learning about the values of rainwater harvesting such as reduced water cost and variety of uses of collected rainwater, participants showed willingness to work with their community to create a set of integrated rainwater harvesting systems within the neighborhoods. These findings offer insight into how rainwater harvesting systems can be an asset to businesses and residents. It also contributes to the existing body of literature by presenting preferred uses of rainwater collected and the users’ attitudes and perceptions towards such systems. Another outcome of this study is a set of recommendations and guidelines on how to approach implementing a series of micro-cores of water collection to support the broader integrated network of rainwater harvesting systems in various land-use categories.
Keywords: Rainwater harvesting; Drought and flooding; Climate change; Preferences; Micro-cores; Integrated network